Transformative and Innovative Leadership: The Key to Successful Teacher Competency Development in Islamic Schools - Hawanuran Syifahaya; Istanto (Ta'dib)
This study aims to analyze the leadership strategies—particularly transformative, participatory, and Islamic value-based approaches—used by the principal in developing human resources at SMP Islam Amanah Ummah. Employing a qualitative case study method, data were collected through in-depth interviews and participatory observation involving one principal and five teachers directly involved in the HR development program. Thematic analysis was used to interpret the data, supported by triangulation and member checking to ensure validity. The findings show that the principal implements structured leadership strategies through annual planning, In-House Training (IHT), internal coaching, and participation in external training. A key innovation is the integration of non-academic training such as public speaking, digital media production, and Islamic health practices. These strategies not only improve pedagogical competence but also enhance teacher motivation and loyalty. A significant challenge identified is resistance to technological adaptation among senior teachers, as well as limited funding and time constraints for intensive training. The most important contribution of this research is the identification of a holistic, Islamic value-based leadership model that promotes both academic and moral development in teachers.